Structure and properties of Nylon 12/SiC nanocomposites. (25th March 2019) - Lua, Xuan; Jin, Yunxue
Abstract: Re-melting well-dispersed SiC nanoparticulate filler in Nylon 12 powder matrix was used to create Nylon 12/SiC nanocomposites, and the effects of different filler contents on the mechanical and thermal properties were investigated. Scanning Electron Microscope (SEM), Transmission Electron Microscopy (TEM) and Micro-CT were used to visualise the morphological features of the composites, the crystallization behaviour and phase transformations were evaluated by TGA and XRD, and the mechanical properties were assessed by utilising tensile, hardness and impact tests. We have found that the samples have tight and neat interface between the matrix and SiC filler, and that for the composites with 7.5% of SiC, their tensile strength and Young's modulus were increased by 47.7% and 4 times, respectively against the plain Nylon 12. The thermal stability becomes more stable for composites with 2.5% and 5% SiC, but decreases for the 7.5% and 10% samples.